2009
DOI: 10.1177/1088767909353020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Changes in the Effect of Divorce Rates on Homicide Rates Across Large U.S. Cities, 1960-2000: Revisiting the Chicago School

Abstract: Researchers commonly include a measure of the level of divorce among the standard covariates in macro-level studies of homicide, justifying this practice with reference to social disorganization theory. We review the underlying logic for a divorce/homicide relationship, distinguishing between a “cultural/normative conflict” variant advanced by the classical Chicago School theorists and a “structural/control” variant associated with the neosocial disorganization perspective. We suggest that the cultural/normati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Second, community economic need, as operationalized by the receipt of public assistance, requires further study to better understand how poverty associates with IPH. Third, divorce rate, rather than operating as a measure of gender equality, seems to be operating as it was classically conceived in social disorganization theory as a disorganizing factor that increased violence in neighborhoods (Beaulieu & Messner, 2010; Sampson & Groves, 1989). Research has indicated that despite changes in social norms, divorce has remained a positive correlate of homicide overall (Beaulieu & Messner, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, community economic need, as operationalized by the receipt of public assistance, requires further study to better understand how poverty associates with IPH. Third, divorce rate, rather than operating as a measure of gender equality, seems to be operating as it was classically conceived in social disorganization theory as a disorganizing factor that increased violence in neighborhoods (Beaulieu & Messner, 2010; Sampson & Groves, 1989). Research has indicated that despite changes in social norms, divorce has remained a positive correlate of homicide overall (Beaulieu & Messner, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There was no missingness in the county-level variables. Gender equality variables were (a) the ratio of the proportion of women to the proportion of men between the ages of 20 and 64 in the labor force, (b) the ratio of the proportion of women to the proportion of men older than 25 with at least 4 years of postsecondary education, and (c) the divorce rate of persons above 15 (Beaulieu & Messner, 2010; Dugan et al, 2003; U.S. Census Bureau, 2018b, 2018c, 2018e).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such ranges suggest that even percent changes of over 100% for large polities are not uncommon and should not per se be considered unexpected simply by chance. Because of this year-to-year variability researchers often aggregate homicide rates over multiple year spans and analyze those (see Beaulieu & Messner, 2010, for one example).…”
Section: Identifying Changes In Homicide Rates Over Timementioning
confidence: 99%
“…Divorce also has been conceptualized as a factor that increases violence risks (Beaulieu & Messener, 2010). Divorce is a disruption in family stability and viewed as a source of weakened social ties.…”
Section: Theory and Hypothesesmentioning
confidence: 99%